ANALISIS TINGKAT PENGUNGKAPAN ESG DISCLOUSURE PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020–2024 - Firdaus, Roykhana; Nawangsari, Ajeng Tita (Jurnal Riset Ilmu Akuntansi, 2026)
This study aims to evaluate the extent of Environmental, Social, and Governance (ESG) disclosure among pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2020– 2024 period. The research adopts a descriptive qualitative approach using content analysis of annual and sustainability reports. The sample consists of six pharmaceutical firms: Kalbe Farma, Kimia Farma, Indofarma, Pyridam Farma, Merck, and Tempo Scan Pacific. The findings reveal that the overall ESG disclosure level in the pharmaceutical sector is relatively high, with an average of 76%. Among the three dimensions, governance is the most consistently reported, followed by social aspects, while environmental disclosure remains the least emphasized. Merck and Kalbe Farma record the highest disclosure levels, whereas Pyridam Farma and Tempo Scan Pacific show the lowest. These results indicate that sustainability reporting within the pharmaceutical industry is still largely voluntary and is influenced by company size and the degree of reputational awareness.